A well – a wellspring – a jewel - Bagina, Elena (project baikal, 2021)
Fresh water in the city is considered as the most important strategic resource for the existence of mankind. The article reveals religious, mythological and everyday symbols of water as a necessary element of national spiritual cultures. It also describes architectural peculiarities of wells as centers of attraction for citizens, meeting places and magic rituals in different regions of the world. The importance of fresh drinking water as an element of urban infrastructure is emphasized.
Keywords: water; city; well; treasure; architecture of wells; beliefs; well symbolism